A visualization technique to assist in the comparison of large meteorological datasets. (May 2022) - Urribarri, Dana K.; Larrea, Martín L.
Abstract: The comparison of meteorological data is a fundamental task within the techniques of meteorological forecasting due to the cyclical nature of the climate. However, interpretation of meteorological datasets can be difficult due to their large size. The goal of information visualization is to support a better understanding of the data what includes assisting the user in the data comparison process. However, few visualization techniques have been specifically developed to support the comparison process of big meteorological data. In this paper, we improved a visualization technique for large time-series comparison. The new technique is more suitable for the comparison of meteorological data. Graphical abstract: Highlights: Overview+Detail comparative visualization for time series of meteorological data. Comparison of the time misalignment of roughly periodic phenomenon using DTW. Detailed visualization based on connected heatmaps. Distance function improved to consider measurements with incompatible units. Color coding along all views considering the degree of misalignment.